Pre-Operative Scapular Rehabilitation for Arthroscopic Repair of Traumatic Rotator Cuff Tear: Results of a Randomized Clinical Trial - Luane Landim de Almeida; Adriano Fernando Mendes Júnior; José da Mota Neto; Leandro Furtado De Simoni; Karine Helena Souza Lopes; Paloma Carvalho Guimarães; Brenda Iasmin de Oliveira Valério; Aaron Sciascia (International Journal of Sports Physical Therapy, 2021)
# Background Pre-operative rehabilitation aims to improve the functional capacity of the individual to enable him/her to prepare for the period of inactivity associated with the surgical procedure.